Effects of pollution load and salinity shock on nitrogen removal and bacterial community in two-stage vertical flow constructed wetlands. (December 2021) - Chi, Zifang; Hou, Lining; Li, Huai
Graphical abstract: Highlights: High nitrogen removal was achieved in TS-VFCW with iron ore and wood chips. Iron ore promoted nitrification and autotrophic denitrification. Wood chips strengthened heterotrophic denitrification. 3% salinity decreased COD and NH4 + -N removal but improved NO3 – -N removal. Ubiquitous denitrifying bacteria under salinity ensured denitrification. Abstract: To understand the denitrification performance and microbial community of two-stage vertical flow constructed wetlands (TS-VFCWs) with iron ore/manganese ore and wood chips, COD and nitrogen removal were investigated under pollution load and salinity shock. High removal of COD (87%), NH4 + -N (97%), and NO3 – -N (98%) were achieved with increasing load, but the high pollutant load inhibited the denitrification performance in TS-VFCW with iron ore and wood chips. TS-VFCW with iron ore and wood chips showed good recovery potential with decreasing load. High NH4 + -N removal was observed in TS-VFCW with manganese ore and wood chips. Treatment with 3% salinity decreased COD and NH4 + -N removal but improved NO3 – -N removal, maintaining relatively good nitrogen removal. The addition of iron ore and manganese ore enriched nitrifying bacteria Flavobacterium and autotrophic denitrifying bacteria, while wood chips promoted heterotrophic denitrification and organic degradation. In addition, ubiquitous denitrifying bacteria under salinity ensured excellent denitrification performance.